PENGARUH TOTAL AKTIVA DAN PENDAPATAN TERHADAP LABA BERSIH (STUDI PERUSAHAAN PERBANKAN LQ 45 BEI) - Muhammad Zulkarnain (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
The study was conducted with the aim of examining the effect of total assets and income on net income of banking companies included in the LQ 45 index. Data used secondary data from 2013-2018 from 6 banking companies included in the LQ 45 index. Data analysis method uses the assumption test classic, multiple linear regression equation, coefficient of determination test (R2), F test and t test. The results of research for multiple linear regression and F test, it is known that total assets and income have a positive and significant effect on net income of banking companies included in the LQ 45 index. The results of the t test of total assets have a significant effect on net income of banking companies but for income has no significant effect to net profit of banking companies included in LQ 45.